1997
DOI: 10.1073/pnas.94.7.2828
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation stimulates the cooperative DNA-binding properties of the transcription factor OmpR

Abstract: The two-component regulatory proteins OmpR and EnvZ of Escherichia coli K-12 regulate expression of the major outer membrane porin protein, OmpF. OmpR is a DNA-binding protein that is involved in both the positive and negative control of ompF transcription. EnvZ is a histidine kinase that phosphorylates OmpR in response to environmental signals. We used DNA migration retardation analysis to examine the interactions of OmpR and the phosphorylated form of OmpR (OmpR-P) with the regulatory region immediately upst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 19 publications
5
51
0
Order By: Relevance
“…In all cases, the phosphorylation of response regulators has been reported to affect their binding to the target promoters, by increasing binding affinity, such as OmpR and PhoB (Aiba et al, 1989;, by changing the DNA binding pattern, such as UhpA (Dahn et al, 1997;Boucher et al, 1997), or by stimulating co-operative binding to DNA, such as NtrC (Porter et al, 1993;Huang et al, 1997), to activate gene transcription. The binding pattern of PhoP to the core binding regions of the pstS and phoA promoters shows similarities to that of UhpA binding to the uhpT promoter, in which there are high-and low-affinity binding sites for the unphosphorylated form of response regulator.…”
Section: Discussionmentioning
confidence: 99%
“…In all cases, the phosphorylation of response regulators has been reported to affect their binding to the target promoters, by increasing binding affinity, such as OmpR and PhoB (Aiba et al, 1989;, by changing the DNA binding pattern, such as UhpA (Dahn et al, 1997;Boucher et al, 1997), or by stimulating co-operative binding to DNA, such as NtrC (Porter et al, 1993;Huang et al, 1997), to activate gene transcription. The binding pattern of PhoP to the core binding regions of the pstS and phoA promoters shows similarities to that of UhpA binding to the uhpT promoter, in which there are high-and low-affinity binding sites for the unphosphorylated form of response regulator.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of multiple shifted bands in these gel shift assays was not surprising, as gel shift studies with OmpR and SarA revealed multiple shifted bands at target promoters (14,27). An identical gel shift reaction with 100 bp of the S. aureus ribosomal protein rpsC did not produce a shifted band, indicating that the SrrA binding to agr, spa, srr, and tst promoters is not due to nonspecific association with staphylococcal DNA.…”
Section: Vol 186 2004mentioning
confidence: 99%
“…The nonphosphorylated form of StyR was shown to be a monomer, but on phosphorylation the two monomers join to form a dimer (124). This is also known to occur in other two-component regulatory systems (37,64,89,129,243). StyR in dimeric form has a 10-fold-higher affinity for the styA promoter than does the monomer (124), which could mean that dimerization of the response regulator is needed for efficient recruitment of the protein on the promoter and subsequent transcription activation.…”
Section: Structure and Conformation Of The Response Regulatorsmentioning
confidence: 99%